Ability emotional intelligence and mental health: Social support as a mediator. (September 2016) - Zeidner, Moshe; Matthews, Gerald
Abstract: The mediating role of perceived social support availability is examined in the observed association between ability emotional intelligence (EI) and psychological distress. 185 Israeli undergraduate students completed measures of ability EI, social support, and distress. As predicted, path analyses demonstrated that social support was a significant mediator of the effects of EI on distress. These data suggest that the adaptive benefits of high EI should be understood from a social perspective. Highlights: Ability EI, measured with the MSCEIT, correlates with well-being and social support. Multivariate models confirm that support fully mediates the EI effect on well-being. Ability EI may be a socially-defined rather than a purely individual construct.